PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN KOMPENSASI RUGI FISKAL TERHADAP TAX AVOIDANCE - Ningsih, Yulia Rahayu; Ferdiansyah, Ferdiansyah (Jurnal Riset Akuntansi Politala, 2024)
This study aims to examine the effect of Corporate Social Responsibility and loss compensation on tax avoidance in property and real estate sub-sector service companies. This type of research is quantitative using secondary population data obtained from the Indonesia Stock Exchange, and company websites for the period 2016-2021 which found 78 companies. The sampling technique in this study was using the Purposive Sampling method with the data analysis technique used was panel data regression analysis by selecting the regression model, classical assumption test and hypothesis analysis method using the Eviews 10 program data processing. Based on the test results, this study states that : based on the F test, Corporate Social Responsibility and fiscal compensation simultaneously have an effect on Tax Avoidance, while through the t test (partial) Corporate Social Responsibility partially has no effect on Tax Avoidance. Fiscal loss compensation has a positive effect on Tax Avoidance